Pengaruh Lifestyle, Percieved Ease of Use dan Kepercayaan Terhadap Keputusan Pembelian pada Toko Pakaian Online - Rika Wahyuni; Hadi Irfani (Psyche 165 Journal, 2019)
The aim of this study was to determine the influence Lifestyle, Percieved Ease of Use and Trust on Purchasing Decisions on Online Fashion Shop. This reserch is quantitative descriptive data and causal analysis, respondents surveyed in this study amounted to 50 people who have made a purchasing on online fashion shop by using purposive sampling. Then carried out analysis to the data obtained by using double regression analysis. Lifestyle significantly influence Purchasing Decisions on Online Fashion Shop, Percieved Ease of Use significantly influence Purchasing Decisions on Online Fashion Shop, Trust significantly influence Purchasing Decisions on Online Fashion Shop. Lifestyle, Percieved Ease Of Use and Trust significantly influence Purchasing Decisions on Online Fashion Shop amounted to 78%. Where as the remainder about 22% described by other variable is not used within this research.